Rapid titration of opiate doses via patient-controlled intravenous analgesia for patients with severe cancer pain. (18th May 2018) - Tian, Suming; Liu, Minjun; Qiao, Shina; Wu, Yue
This study was to investigate the feasibility and safety of patient-controlled intravenous analgesia for opiate titration in patients with severe cancer. Eligible patients with cancer pain were randomly divided into two groups, which were titrated with a subcutaneous injection of morphine and patient-controlled intravenous analgesia, respectively. The time required for patients to begin titration to reach visual analog scale score ⩽ 3, the adverse reactions during titration, the time spent by nurses in titrating each patient, and the time to complete the titration with a delayed-release dosage form analgesic effect and adverse reaction. The mean titration time of patient-controlled intravenous analgesia group (1.09 ± 0.82 vs 2.97 ± 1.98) and morphine dosage (18.78 ± 12.32 vs 13.23 ± 8.07) were significantly lower than those in the subcutaneous group ( P  < 0.05). The incidences of nausea, vomiting, pruritus, urinary retention, and sedation in the subcutaneous injection group were significantly lower than those in the subcutaneous injection group ( P  < 0.05). The assessment times of the two groups (10.19 ± 3.72 vs 10.25 ± 4.88) were similar ( P  > 0.05). However, the time required for subcutaneous injection in patients under patient-controlled intravenous analgesia was significantly lower than that in the subcutaneous injection group (36.36 ± 12.15 vs 132.36 ± 32.79), which was statistically significant ( P  < 0.05). After the titration, the controlled release opioid was used to treat cancer pain. The visual analog scale score of the patient-controlled intravenous analgesia group was significantly lower than that of the subcutaneous group (2.44 ± 1.37 vs 2.73 ± 0.91) at 7 days after treatment in the subcutaneous group (1.05 ± 0.30 vs 2.45 ± 1.29; P  < 0.05). Patient-controlled intravenous analgesia technique can effectively and quickly complete the titration of cancer pain treatment with less occupational care resources and is better than the subcutaneous injection titration.